0
$\begingroup$

I have the function $$f(x)=\frac{2x}{10+x}$$ and I am asked to find its power series representation which I found to be $$\sum_{n=0}^{\infty} (-1)^{n} *\frac{2x^{n+1}}{10^{n+1}}$$ and I found the radius of convergence to be $R=10$. All until here is clear and easy, but when I am asked to find the 1st few terms I tries to do the following

  • $c_0$ I plugged a value of $x=0$ in my original function $f(x)$ which equals $(0)$ [correct answer]

  • $c_1$ I plugged a value of $x=0$ in the 1st derivative of $f(x)$ which equals $\frac{1}{5}$ [correct answer]

  • $c_2$ I plugged a value of $x=0$ in the 2nd derivative of $f(x)$ [incorrect answer]

  • $c_3$ I plugged a value of $x=0$ in the 3rd derivative of $f(x)$ [incorrect answer]

  • $c_4$ I plugged a value of $x=0$ in the 4th derivative of $f(x)$ [incorrect answer]

So if $c_0$ and $c_1$ are correct why would the others not be as well? Am I missing something profoundly important?

$\endgroup$
  • $\begingroup$ You're forgetting the factor of $\frac1{n!}$ in the coefficients. This doesn't matter for $c_0$ and $c_1$ since $0! = 1! =1$. $\endgroup$ – Santiago Canez Aug 12 '15 at 16:49
3
$\begingroup$

$$\dfrac{2x}{10+x}=\dfrac{2x}{10\left(1+\dfrac x{10}\right)}=\dfrac x5\left(1+\dfrac x{10}\right)^{-1}$$

For $\left|\dfrac x{10}\right|<1,$ $$\left(1+\dfrac x{10}\right)^{-1}=\sum_{r=0}^\infty\left(-\dfrac x{10}\right)^r$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.